How do firms manage their interest rate exposure?. Issue 5 (27th November 2019) - Hecht, Andreas
Abstract : Purpose: This paper aims to identify how non-financial firms manage their interest rate (IR) exposure. IR risk is complex, as it comprises the unequal cash flow and fair value risk. The paper is able to separate both risk types and investigate empirically how the exposure is composed and managed, and whether firms increase or decrease their exposure with derivative transactions. Design/methodology/approach: The paper examines an unexplored regulatory environment that contains publicly reported IR exposure data on the firms' exposures before and after hedging. The data were complemented by indicative interviews with four treasury executives of major German corporations, including two DAX-30 firms, to include professional opinions to validate the results. Findings: The paper provides new empirical insights about how non-financial firms manage their interest rate exposure. It suggests that firms use hedging instruments to swap from fixed- to floating-rate positions predominantly in the short-to medium-term, and that 63 [37] per cent of IR firm exposure are managed using risk-decreasing [risk-increasing/-constant] strategies. Practical implications: Interviewed treasury executives suggest that the advanced disclosures benefit various stakeholders, ranging from financial analysts and shareholders to potential investors through more meaningful analyses on firms' risk management activities. Further, the treasury executives indicate that the new data granularity would enable firms to carry out unprecedented competitive analyses and thereby benchmark and improve their own risk management. Originality/value: The paper is the first empirical study to analyze the interest rate activities of non-financial firms based on actually reported exposure data before and after hedging, rather than using proxy variables. In addition, the new data granularity enables a separate analysis of the cash flow and fair value risk to focus on the non-financial firms' requirements.